PENGEMBANGAN LKPD BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) MELALUI STUDI KASUS KUALITAS AIR SUNGAI BEKRI AKIBAT LIMBAH PABRIK PTPN 7 UNTUK MATERI POKOK PERUBAHAN LINGKUNGAN KELAS X - Pratiwi, Nurwita; Asih, Triana; Sujarwanta, Agus (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
The purposes of this research are 1)produced LKPD (Students’s workseet) based on PBL learning models. 2) to utilize natural resources in the form of the Bekri River which can be used as learning media for students. The research was carried out through 4 stages, that is defining, design, development, and dissemination. In the define stage, the researcher conducted a survey at MA Bustanul Ulum Jaya Sakti for seeking the problems that occurred through interviews and observation steps with Biology subject teachers. In the design phase, the researcher compiles the LKPD (Students' Worksheet) development plan to be developed. In the development phase, the researcher produced LKPD (Students' Worksheet) based on PBL learning models on the subject matter of environmental change. At this stage, the validation process of the product feasibility was also carried out by material experts, subject teachers, design experts, and the trial process for students at MA Bustanul Ulum Jaya Sakti. The percentage results obtained from the validation of material experts by 88% -92%, design experts by 90% -94%, subject teachers 92%, and student trials by 84% -94%, this states that the LKPD (Students' Worksheet) developed is feasible to be used in the learning process.